Contextual Learning on Mathematical Subjects to Enhance Student Motivation for Learning in Vocational High School - Andes Safarandes Asmara; Hardi Hardi; Yusi Ardiyanti (Jurnal Pendidikan Indonesia, 2019)
The problem of learning in mathematics is because students always look at mathematics is difficult and usually exacerbated by the use of minimal learning aids. It needs to be given a fun learning solution for students to have the motivation and willingness to learn mathematics.  One of them is contextual learning. This research wants to see the extent to which contextual learning is able to improve student learning motivation. This study uses qualitative research with the type of action research class (PTK) using the implementation cycle to see increased motivation and student learning outcomes. The results showed an increase in the motivation percentage of learning to study as a whole for each indicator of the I cycle of 62, 89% to 73.42% motivation to study in cycle II for learning outcomes experienced Increase in high category with gain Sebsar 0.71. Based on the data it has been noted that with contextual learning it is able to improve student motivation and learning outcomes.